Municipal pleural cancer mortality in Spain. Issue 3 (21st February 2005) - López-Abente, G; Hernández-Barrera, V; Pollán, M; Aragonés, N; Pérez-Gómez, B
Abstract : Background: Pleural cancer is a recognised indicator of exposure to asbestos and mesothelioma mortality. Aims: To investigate the distribution of municipal mortality due to this tumour, using the autoregressive spatial model proposed by Besag, York, and Molliè. Methods: It was possible to compile and ascertain the posterior distribution of relative risk on the basis of a single Bayesian spatial model covering all of Spain's 8077 municipal areas. Maps were plotted depicting standardised mortality ratios, smoothed relative risk (RR) estimates, and the distribution of the posterior probability that RR >1. Results: There was a higher risk of death due to pleural cancer in well defined towns and areas, many of which correspond to municipalities where asbestos using industries once existed for many years, the prime example being the municipal pattern registered for Barcelona Province. The quality of mortality data, the suitability of the model used, and the usefulness of municipal atlases for environmental surveillance are discussed.